User Primacy in Corporate Financial Reporting: A Social Contract Approach. - Gaa, James C. (The Accounting Review, 1986)
Abstract ABSTRACT: According to the principle of user primacy, the interests of users of financial reports take priority over the interests of preparers of financial reports. When applied to the activities of a standard setter for corporate financial reporting, user primacy is a constitutional claim, stating a general principle for the resolution of conflicts. It is controversial, because it is incompatible with views that standard setting is a collective choice process, where the interests (preferences) of all parties are to count equally. An analysis of the logical foundations of the principle is provided, based on recent work in ethics and social and political philosophy. User primacy is a distributional principle governing the relationship between users and managers. A theoretical framework for the rational choice of a distributional principle governing the disclosure of information in the securities market is provided. The conditions under which a securities market–which includes in its basic structure a standard setter to implement the user primacy principle–would be chosen by rational, disinterested securities market agents are analyzed. A standard setter would be established to enforce user primacy, thereby redressing an imbalance between investors (users) and managers. By acting in accordance with this principle, the standard setter aids all securities market agents in exploiting the potential trading gains provided by such a market. At the same time, investors are protected from possible losses arising from the basic relationship between them and managers of widely held corporations. The analysis is applied to two versions of the user primacy principle prominent in the professional standard-setting literature. Although the analysis is not intended to advocate user primacy, a clear and complete statement of the principle is proposed as a guide to...